Bugis-Makassar Local Wisdom As A Foundation For Religious Moderation Education: A Multi-Site Study In Islamic High Schools - Ardiyansyah; Tabrani, Ahmad; Sanifu; Rofiq, Machbub Ainur; Zamroni, M Afif; Rahmat (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Religious moderation is a significant issue in Islamic education in Indonesia, particularly in shaping a young generation that is inclusive, tolerant, and respectful of diversity. This study aims to identify and analyze the values of religious moderation reflected in the life philosophy of the Bugis-Makassar community, as well as to examine efforts to develop these values at PP Babul Khaer Private Islamic Senior High School and State Islamic Senior High School 1 Bulukumba. Values such as tolerance, balance (tawazun), justice, and respect for plurality are not only rooted in Islamic teachings but also align with Bugis-Makassar local wisdom, including siri’ na pacce (upholding personal and communal honor), sipakatau (mutual humanization). Types of multi-site qualitative research. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using triangulation techniques. The findings reveal that the promotion and reinforcement of students’ religious moderation in Islamic schools are not conveyed solely through religious approaches but are also integrated with the cultural values of Bugis-Makassar local wisdom. This indicates that Bugis-Makassar philosophy is not only relevant but also plays a strategic role in the internalization of religious moderation values in the school environment. These values are incorporated into both the curriculum and extracurricular activities, fostering students with inclusive, tolerant attitudes and respect for plurality. The contribution of this study lies in strengthening strategies for religious moderation education based on local wisdom while affirming that Indonesia’s cultural heritage is closely aligned with the values of moderate and tolerant Islamic education